Microbial composition of egg component and its association with hatchability of laying hens - Jin, Jiaming; Zhou, Qianqian; Lan, Fangren; Li, Junying; Yang, Ning; Sun, Congjiao (Frontiers in Microbiology, 2022)
The internal quality of eggs is critical for human consumption and embryonic development. However, microorganisms inside eggs have not been thoroughly investigated for their roles in determining the egg’s internal quality. Here, a total of 21 hens were selected from more than 1,000 chickens based on their hatching results and were divided into high- and low-hatchability groups. Then, we collected 72 eggs from these 21 hens to obtain egg whites and yolks, including 54 fresh eggs and 18 eggs after 12 days of incubation. We characterized the microbial composition of egg yolks and whites, the microbial change along incubation, and differences in microbial abundance between the high- and low-hatchability groups. The results indicated that egg whites are not sterile. Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes were the dominant phyla in egg yolk and white. There was a large difference in the microbial composition between egg whites and yolks, and this difference increased after 12 days of incubation. Egg whites have lower microbial diversity than egg yolks owing to the presence of antibacterial substances such as lysozyme in the egg white. After a 12-day incubation, the microbial diversity decreased in egg whites but increased slightly in egg yolks. Meanwhile, the microbes in egg white can migrate to egg yolk during incubation. Additionally, Genus Muribaculaceae was identified as a biomarker in egg yolks incubated for 12 days and was more often detected in healthy groups. On the contrary, more genus Rothia were found in the fresh egg yolk of the low hatchability groups and was considered to have low virulence. These findings shed light on the composition and differences in microbiota between egg yolks and whites and may open new avenues for studying embryonic development in chickens.